The elasticity of taxable income: Estimates and flat tax predictions using the Hungarian tax changes in 2005 - Péter Bakos; Péter Benczúr; Dóra Benedek (Magyar Nemzeti Bank, 2008)
Many Central and Eastern European countries are adopting flat tax schemes in order to boost their economies and tax revenues. Though there are signs that some countries do manage to improve on both fronts, it is in general hard to distinguish the behavioral response to tax changes from the effect of increased tax enforcement. This paper addresses this gap by estimating the elasticity of taxable income in Hungary, one of the outliers in terms of not having a flat tax scheme. We analyze taxpayer behavior using a medium-scale tax reform episode in 2005, which changed marginal and average tax rates but kept enforcement constant. We employ a Tax and Financial Control Administration (APEH) panel dataset between 2004 and 2005 with roughly 215,000 taxpayers. Our results suggest a relatively small but highly significant tax price elasticity of about 0.06 for the population earning above the minimum wage (around 70% of all taxpayers). This number increases to around 0.3 when we focus on the upper 20% of the income distribution, with some income groups exhibiting even higher elasticities (0.45). We first demonstrate that such an elasticity substantially modifies the response of government revenues to the 2004-2005 tax changes, and then quantify the impact of a hypothetical flat income tax scheme. Our calculations indicate that though there is room for a parallel improvement of budget revenues and after-tax income, those gains are modest (2% and 1.4%, respectively). Moreover, such a reform involves important adverse changes in income inequality, and its burden falls mostly on lower-middle income taxpayers.
Keywords: H24; H31; 330; elasticity of taxable income; tax reform; behavioral response; revenue estimation; flat tax; Einkommensteuer; Einkommenselastizität; Steuerbelastung; Steuerreform; Flat Tax; Schätzung; Ungarn